Spring migratory routes and stopover duration of satellite‐tracked Eurasian Teals Anas crecca wintering in Italy. (27th April 2018) - Giunchi, Dimitri; Baldaccini, Natale E.; Lenzoni, Alfonso; Luschi, Paolo; Sorrenti, Michele; Cerritelli, Giulia; Vanni, Lorenzo
Abstract : Identifying an organism's migratory strategies and routes has important implications for conservation. For most species of European ducks, information on the general course of migration, revealed by ringing recoveries, is available, whereas tracking data on migratory movements are limited to the largest species. In the present paper, we report the results of a tracking study on 29 Eurasian Teals, the smallest European duck, captured during the wintering period at three Italian sites. The departure date of spring migration was determined for 21 individuals, and for 15 the entire spring migratory route was reconstructed. Most ducks departed from wintering grounds between mid‐February and March following straight and direct routes along the Black Sea‐Mediterranean flyway. The breeding sites, usually reached by May, were spread from central to north‐Eastern Europe to east of the Urals. The migratory speed was slow (approximately 36 km/day on average) because most birds stopped for several weeks at stopover sites, mainly in south‐eastern Europe, especially at the very beginning of migration. The active flight migration segments were covered at much higher speeds, up to 872 km/day. Stopover duration tended to be shorter when birds were closer to their breeding site. These results, based on the largest satellite tracking effort for this species, revealed for the first time the main features of the migratory strategies of individual Teals wintering in Europe, such as the migration timing and speed and stopover localization and duration.